Evidências do uso do lean em processos acadêmico-administrativos em instituições de educação superior privadas - Nascimento, Anete Petrusch do (Universidade do Vale do Rio dos Sinos, 2014)
This research aims to find evidences of the use of Lean in private Higher Education Institutions (HEIs) in Brazil, specifically in the academic and administrative services provided to the students of these institutions. For that, it first seeks to identify the degree of adoption of Lean in these organizations through a survey addressed to all private universities and colleges in the country. The results of this survey indicate that there may be some initiatives, but they occur more as a result of isolated actions, than institutionalized ones. A second aim contributes to the broader issue of this research by investigating one of Lean most central concept applied to academic and administrative services: if value is in the core of Lean proposal along with waste reduction, then what do students attribute value to in such services? In order to answer this question group interviews with undergraduates and graduate students of different programs and institutions were held. The content analysis of the interviews identified eight attributes of value: Reliability, Care, Access, Responsiveness, Information and Communication Technologies (ICT) Solutions, Communication, Customization and Invisibility. Depending on the kind of service, the value attributes emphasis changes. In addition, in search for empirical evidences of the application of Lean’s tools and principles in a university environment, an action research analysed two real processes in a large community private university located in the state of Rio Grande do Sul, Brazil. The first process concerns the service provided to students with difficult to access to Wi-Fi at the University. The second process refers to adjustments made in the student’s registration due to the cancellation of courses after online registration. In the practical application through Kaizen seminars and an analysis of what happened before, during and after these seminars, it became clear that Lean applies and is suitable to the university context, as it has already been indicated by research conducted in academic institutions abroad. However, the action research also revealed that, if there is no specific effort management and a favorable Lean culture promotion, the mere toolbox application will not guarantee their survival in the institution. This fact is also confirmed by the literature which investigates the effectiveness of Lean in organizations. This work aims to contribute to the discussion of Lean Service, an area still in need of further research, and Lean applied to higher education services, as there is no evidences of previous research on this topic conducted in Brazil. In addition to that, it hopes to contribute to the understanding of the Lean concepts and techniques by the university environment as a way to make the academic and administrative processes more efficient and the value proposition closer to what the student expects and values.
Keywords: Melhoria de processos; Instituições de educação superior (IES); Lean; Sistema Toyota de Produção; Lean service; Processes improvement; Higher education institutions (HEIs); Toyota Production System; ACCNPQ::Engenharias::Engenharia de Produção